Problem of Unemployment in Turkiye at the Focus of Unemployment of Educated People and Underutilisation (1991-2023) - Ali Osman Balkanlı (Siyasal: Journal of Political Sciences)
In societies, unemployment is both an economic, social, and political problem. For this reason, to reduce unemployment is among the main goals of governments all over the world. When it think with Okun Act, this target is also related to economic growth. This goal has always been a valid goal. However, during the development process of the world economy after the 1990s and the 2000s, the production conditions and importance of the workforce have changed significantly compared to the past. In order to analyse the unemployment experienced in the world economy and in Turkiye after 1990, it is necessary to analyse this change process experienced by the world economy. In this context, the first part of this paper is devoted to examining basic concepts such as labour force, employment, and unemployment, and examining changes in the world economy. In the second part of this article, the development of unemployment in terms of countries, country groups, and Turkiye in the world economy in the 1990s and thereafter, and the development of the resources allocated to education in terms of GDP, public expenditures and labour underutilisation are examined. Because of this investigation, it has been determined that unemployment in Turkiye has a chronic increasing trend from 1991 to 2023 but in here especially underutilisation and educated people’s unemployment has increased more intensively.